Analysis of Human Resource Management in The Digital Era Moderated by The Millennial Generation - Ade Jaya Sutisna; Ratih Pratiwi; Karsim Karsim; Siti Zulaika; Machin Machin (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research aims to analyze human resource management in the digital era, with a focus on how it is moderated by the millennial generation among lecturers in the Master of Management program at Semarang University. The analysis is based on indicators such as planning, implementation, assessment, and achievement of performance within the context of digitalization, all moderated by the millennial generation. A random sampling method was employed, resulting in a sample size of 97. Data analysis was conducted using SPSS. According to the SPSS output, hypothesis 1 regarding the impact of planning on performance, hypothesis 2 regarding the impact of implementation on performance, and hypothesis 3 regarding the impact of assessment on performance all show significant effects. Hypothesis 4 indicates a strong impact of achievement on performance. The fifth hypothesis, which examines the millennial generation's influence on performance, is highly relevant. Hypothesis 6 suggests that the notable influence of the millennial generation mitigates the impact of performance planning. Hypothesis 7 posits that the effects of implementation on performance are muted by the millennial generation. Hypothesis 8 indicates that the millennial generation has a major impact on moderating the role of assessment on performance. Finally, hypothesis 9 addresses the moderating role of the millennial generation in the relationship between achievement and performance.